A utilização da termografia na análise macroergonômica na atividade de reboco de teto - Franchini, Aline Sias (2017)
The tasks performed in the construction industry are, in the great majority, handy and with a certain degree of effort. This study had as main objective to evaluate the posture and musculoskeletal overload in the activity of ceiling plastering, which was reported as fatiguing by many workers. For the development of the research, a methodology based on interviews, questionnaire application, filming, work posture evaluation and muscular overload was used using ergonomic tools such as OWAS (Ovako Working Posture Analysis System), Moore Garg (Stain Index) and Checklist of Couto. For the initial evaluation of pain zones and pain intensity, the Diagram of Painful Areas proposed by Corlett and Manenica was used as it is an easy-to-use instrument and can offer answers regarding the existence of pain, its location and its intensity. The positions of the masons were evaluated initially in the activities of subfloor, slab, trowel, azulejo, plaster of ceiling, plaster, wall plaster and servant activities. The postures were analyzed through photographic records and the application of ergonomic tools. The results showed that the activity of the bricklayer towing the roof was the most critical activity, since it presented a greater degree of discomfort, according to the workers and their biomechanical risks. Having discovered the activity of the mason where it required greater overload and pain / discomfort, we set out to the thermographic analysis of this activity in individuals in a controlled environment, in order to verify the efficiency of the thermography in the detection of muscular overload in the shoulder region Of volunteers. The results of the simulations showed that when performing the right shoulder abduction movement, position of the ceiling plaster activity, there was a significant increase in the temperature between the two shoulders as well as the appearance of muscular fatigue at the end of the 350 repetitions of the movement. At the end of this research it is possible to affirm that the use of surface thermography as a complementary tool was an efficient method to implant in an ergonomic program in the company, carrying out a prevention work, avoiding pathologies and improving workers' quality of life. One can contribute considerably to the implantation of the ergonomics in the company, from the reliable diagnosis to the real problems present in the same and often hidden. It is concluded that muscular exigency points can be measured through thermography, in the prevention factor in a work environment in the civil construction.